Effects of road infrastructure on forest value across a tri-national Amazonian frontier. (November 2015) - Baraloto, Christopher; Alverga, Paula; Quispe, Sufer Baéz; Barnes, Grenville; Chura, Nino Bejar; da Silva, Izaias Brasil; Castro, Wendeson; da Souza, Harrison; de Souza Moll, Iracema Elisabeth; Del Alcazar Chilo, Jim; Linares, Hugo Dueñas; Quispe, Jorge Gárate; et al.
Abstract: Road construction demonstrably accelerates deforestation rates in tropical forests, but its consequences for forest degradation remain less clear. We estimated a series of forest value metrics including components of biodiversity, carbon stocks, and timber and non-timber forest product resources, along the recently paved Inter-Oceanic Highway (IOH) integrating Brazil and Peru along the Bolivian border. We installed 69 vegetation plots in intact terra firme forests representative of local community holdings near and far from the IOH, and we characterized 15 components of forest value for each plot. We observed strong geographic gradients in forest value components across the region, with increases from west to east in aboveground biomass and in the abundance of timber and non-timber forest product trees and regeneration. Plots in communities in Pando, Bolivia, where the IOH remains in part unpaved, had the highest aboveground biomass, standing timber volumes and Brazil nut tree density. In contrast, communities in Madre de Dios, Peru, where settlements and unpaved portions of the IOH have existed for decades, and in Acre, Brazil, where paving of the IOH has been underway for more than a decade, were more degraded. Seven of the fifteen forest value components we measured increased with increasing distance from the IOH, although the magnitude of these effects was weak. Landscape scale remote sensing analyses showed much stronger effects of road proximity on deforestation. We suggest that remote sensing techniques including canopy spectral signatures might be calibrated to characterize multiple components of forest value, so that we can estimate landscape scale impacts of infrastructure developments on both deforestation and forest degradation in tropical regions.